Berbamine hydrochloride inhibits bovine viral diarrhea virus replication via interfering in late-stage autophagy - Wang, Jun; Yang, Guanghui; Zhang, Linlin; Zhang, Jialu; Wang, Jing; Zou, Yunjing; Wang, Jiufeng (Virus research, 2022)
Bovine viral diarrhea virus (BVDV) is a harmful pathogen that easily causes large-scale infections and huge economic losses to the cattle industry. Berbamine hydrochloride (BBH) is a natural product extracted from berberis and has a wide range of pharmacological effects. However, the antiviral effect of BBH against BVDV needs to be further elucidated. This study aimed to evaluate the antiviral activities of BBH against BVDV infection. We mainly used RT-qPCR, Western blotting, immunofluorescence, and TEM assays to assess the inhibitory activity of BBH against BVDV. The results showed that BBH had an inhibitory effect on BVDV and higher inhibitory activity in the viral attachment and release in MDBK cells. This study found that BVDV could induce and use autophagy to replicate itself. Further results showed that BBH inhibited BVDV infection by inhibiting autophagy integrity in BVDV-infected cells, which was proven by the detection of autophagy-related proteins. Our data show that in BBH-treated BVDV-infected cells, the expression of p62 and LC3 increased over time. After the addition of an autophagy inhibitor, chloroquine (CQ), and an autophagy promoter, rapamycin (Rapa), we found that promoting autophagy was beneficial to the replication of BVDV, while inhibiting autophagy could reduce the number of infections by BVDV, which was evidenced by the expression of the BVDV E2 protein. Furthermore, BBH blocked the normal binding of LC3 and LAMP1 in BVDV-infected cells. In conclusion, BBH inhibited BVDV infection by inhibiting BVDV-induced autophagy in cells, and its inhibitory effect was obvious in the viral attachment and release stages. Therefore, our study provides a new idea for exploring novel anti-BVDV drugs.